2017
DOI: 10.1039/c7ra01038a
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Barbier-type allylation of ketones using allyl halide and indium in water

Abstract: We disclose herein an efficient enantioselective Barbier-type allylation of ketones using allyl halide and indium metal in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…Loh and Zhou reported the first example of enantioselective allylation of aldehydes using indium species in aqueous media, in which ( S , S )‐2,6‐bis(4‐isopropyl‐2‐oxazolin‐2‐yl)pyridine was used as a chiral source . More recently, the Nakamura's research group reported enantioselective allylation of ketones using allylindium reagent prepared from allyl bromide and indium metal (Scheme a) . Their reaction system, to the best of our knowledge, provided the most successful result on the reaction with ketones in pure water, giving the adduct with up to 89% ee.…”
Section: Introductionmentioning
confidence: 99%
“…Loh and Zhou reported the first example of enantioselective allylation of aldehydes using indium species in aqueous media, in which ( S , S )‐2,6‐bis(4‐isopropyl‐2‐oxazolin‐2‐yl)pyridine was used as a chiral source . More recently, the Nakamura's research group reported enantioselective allylation of ketones using allylindium reagent prepared from allyl bromide and indium metal (Scheme a) . Their reaction system, to the best of our knowledge, provided the most successful result on the reaction with ketones in pure water, giving the adduct with up to 89% ee.…”
Section: Introductionmentioning
confidence: 99%
“…Chiral alcohols can be synthesized via (1) multistep transformations from a chiral pool such as terpenes, amino acids, and carbohydrates (Fan et al., 2019, Hung et al., 2019, Brill et al., 2017) or (2) kinetic resolution of racemic alcohols or their derivatives (Liu et al., 2019, Selier et al., 2019, Zhang and Ma, 2018). In addition, asymmetric synthesis such as reduction or nucleophilic addition of prochiral carbonyls recently has been developed (Neves-Garcia et al., 2018, Tsai et al., 2018; Bieszczad and Gilheany, 2017, Nakamura et al., 2017). Although HPLC and GC with chiral stationary phases are commonly used for chiral analysis of alcohols as a reliable direct analytical technique, derivatization of alcohols such as introducing chromophores, polar functional groups, or hydrophobic units is often necessary for the desirable analytical results.…”
Section: Resultsmentioning
confidence: 99%
“…In 2017, Nakamura reported an indium‐catalyzed asymmetric Barbier‐type allylation of ketones in aqueous media (Scheme 42). [ 93 ] Indium powder was used to reduce the allylic bromide in situ, which avoided usage of highly toxic organotin or moisture‐ sensitive reagents such as Grignard reagents and silanes.…”
Section: Tridentate Imidazoline Ligandsmentioning
confidence: 99%